Low-cost modular systems for agarose gel documentation - Alfredo G Gonzalez; Maribel González-García; Rafael Pérez-Ballestero (BioTechniques, 2022)
While conducting recombinant DNA technology procedures, such as DNA purification, agarose gel electrophoresis is often used for identification, characterization and quantification of DNA. The collection of data for experiments involving such techniques frequently involves capturing images using systems that are expensive and/or proprietary, such that they are not user-serviceable when they malfunction or become antiquated. In response to these limitations, work was done to replace the authors' existing aging Mac OS-based modular system with open-source software and generic hardware. Several versions of a modular imaging system that can be adjusted to fit nearly all use cases are described. The systems developed can accommodate diverse uses from research laboratories to educational environments where commercial systems could be unaffordable.